Peran Teknologi Informasi dan Komunikasi dalam Penguatan Pendidikan Karakter: Tinjauan Pustaka Sistematis - Melanie putri; Muhammad Redha Anshari (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
The digital era has brought significant changes in the world of education, especially in strengthening the character of students. This study aims to identify the role of information and communication technology (ICT) in strengthening character education through a Systematic Literature Review (SLR) approach to five selected relevant journal articles published in the last five years. The results of the analysis show that ICT can be strategically utilized in instilling character values such as honesty, responsibility, discipline, empathy, and integrity. The implementation of ICT through learning platforms, digital applications, and technology-based literacy movements has proven to be able to create learning experiences that are morally charged as well as fun. However, the use of ICT also presents challenges such as cyberbullying and misuse of technology that need to be anticipated with digital literacy and ethical mentoring. This research recommends the wise and contextual integration of ICT in character learning to form a generation with strong character and adaptive to the times.